Mechanisms regulating cytochrome c release in pancreatic mitochondria - Odinokova, IV (Gut, 2008)
BACKGROUND: Mechanisms of acinar cell death in pancreatitis are poorly understood. Cytochrome c release is a central event in apoptosis in pancreatitis. Here, we assessed the regulation of pancreatic cytochrome c release by Ca(2+), mitochondrial membrane potential (ΔΨm), and reactive oxygen species (ROS), the signals involved in acute pancreatitis. We used both isolated rat pancreatic mitochondria and intact acinar cells hyper-stimulated with cholecystokinin-8 (CCK-8; in vitro model of acute pancreatitis). RESULTS: Micromolar amounts of Ca(2+) depolarised isolated pancreatic mitochondria through a mechanism different from the “classical” (ie, liver) mitochondrial permeability transition pore (mPTP). In contrast with liver, Ca(2+)-induced mPTP opening caused a dramatic decrease in ROS and was not associated with pancreatic mitochondria swelling. Importantly, we found that Ca(2+)-induced depolarisation inhibited cytochrome c release from pancreatic mitochondria, due to blockade of ROS production. As a result, Ca(2+) exerted two opposite effects on cytochrome c release: Ca(2+) per se stimulated the release, whereas Ca(2+)-induced depolarisation inhibited it. This dual effect caused a non-monotonous dose-dependence of cytochrome c release on Ca(2+). In intact acinar cells, cytochrome c release, caspase activation and apoptosis were all stimulated by ROS and Ca(2+), and inhibited by depolarisation, corroborating the findings on isolated pancreatic mitochondria. CONCLUSIONS: These data implicate ROS as a key mediator of CCK-induced apoptotic responses. The results indicate a major role for mitochondria in the effects of Ca(2+) and ROS on acinar cell death. They suggest that the extent of apoptosis in pancreatitis is regulated by the interplay between ROS, ΔΨm and Ca(2+). Stabilising mitochondria against loss of ΔΨm may represent a strategy to mitigate the severity of pancreatitis.